Traditional Chinese Medication Tongxinluo Attenuates Lipidosis in Ox-LDL-Stimulated Macrophages by Enhancing Beclin-1-Induced Autophagy - Chen, Yifei; Yu, Fangpu; Zhang, Yu; Li, Mengmeng; Di, Mingxue; Chen, Weijia; Liu, Xiaolin; Zhang, Yun; Zhang, Mei (Frontiers in Pharmacology, 2021)
Tongxinluo (TXL), a traditional Chinese medication, plays a key role in the formation and progression of plaques in atherosclerosis. The formation of foam cells by macrophages accelerates the destabilisation of plaques. In previous research, we had found that TXL significantly inhibits ox-LDL-induced apoptosis in macrophages in vitro by improving the dissociation of the Beclin-1-Bcl-2 complex. Therefore, here, we explored the effect of TXL on lipid metabolism in macrophages and the mechanism involved. To evaluate the role of TXL in atherosclerotic plaques, we construct the atherosclerotic animal model with lentiviral injection and performed immunofluorescence staining analysis in vivo. Western blot, immunofluorescence staining and microscopy were performed to elucidate the mechanism underlying TXL-mediated regulation of autophagy in THP-1 macrophages in vitro. Immunofluorescence assay revealed that TXL treatment inhibited lipid deposition in advanced atherosclerotic plaques. In vitro TXL treatment inhibited lipid deposition in THP-1 macrophages by enhancing autophagy via Beclin-1. TXL reversed the high expression of class I histone deacetylases (HDACs) induced by ox-LDL (p < 0.05). Compared with the TXL + ox-LDL group, TXL failed to promote intracellular lipid droplet decomposition after the addition of the histone deacetylase agonist. We found that TXL attenuates the accumulation of lipids in macrophage by enhancing Beclin-1-induced autophagy, and additionally, it inhibits the inhibitory effect of class I HDAC on the expression of Beclin-1.